Effects of vitamin deficiency (A, C and D) in maternal on the weights of newborns - Abeer Talib Abdulqader (Tikrit Journal of Pure Science)
The present study was designed to find the relation between vitamin deficiency (A, C and D) of maternal and the weights of newborns. The study used 50 volunteers (40 pregnant women with vitamins deficiency and 10 pregnant women without vitamins deficiency). Pregnant women were divided to two groups according to vitamins state. Newborn weights directly were reported at birth time. Vitamins levels showeddecreased invitamin A, vitamin C and vitamin D in 40 pregnant female and normal in 10 pregnant female. Where, Vitamins levels showedsignificant decreased (P<0.05) 40 pregnant female 10 pregnant femalecompared with 10 normal pregnant female. Also, results show a high correlation between decreased vitamins levels and newborn weights. It was concluded from this study that the vitamins deficiency (A, C and D) in maternal led to decreased the weights of newborn.